Et lite kommunalt bibliotek mot en global pandemi - Bærø, Anna (UiT Norges arktiske universitet, 2022)
This thesis deals with Karlsøy Municipality, and its local public library and how it has fared during the global Covid-19 pandemic. Through my research methods, conversations with employees and personal experiences at the library, has revealed that there are several aspects of the library that stands out in comparison to larger libraries. For this thesis, I have considered several methods, some qualitative and some quantitative. Interviews with three key positions at the library, librarian, archivist and a regular user have concluded that lock-down and infection control have made the library and librarian less accessible. With a population that is to a greater extent defined as risk groups, and with the nursing home as the center, society has been strict in protecting these residents. We also have a librarian who are themselves in the risk group, who is also not a resident of the municipality. Thus, one has a mixture of shortages of both employees and users. The library has been completely closed for periods; the librarian has worked from home in large portions of the time, which have greatly affected physical work tasks. The lack of digital solutions has also made the library more inaccessible, but one must consider that the population with its large proportion of older people, might prefer the more "old-fashioned" forms of literature. A lot of time has also passed since the library was open, but without a librarian present. Users have become accustomed to an everyday life without such assistance, and it is important to regain contact between user and librarian. The pandemic has left its mark on our society, and is still a part of our lives, but it is clear that the people are ready to move on and back to a more normal everyday life. With the library reopened, and with a more present librarian, I put forward several suggestions for solutions to optimize the library and turn it into a larger social and cultural meeting point in the center of society.